Observations on parasites of Epinephelusmalabaricus (Bloch and Schneider) - Haq, M A Badul; Srinivasan, M; Murugan, M (Indian Journal of Fisheries, 2011)
Cage culture of Epinephelus malabaricus in fixed net cages was carried out inthe south east coast of India. Fishes were fed with different diets like, prawnwaste head, Sardinella longiceps, squid waste, crab (Portunus spp.) and beefliver. During 184 days culture, several types of parasites were observed andstudied. External parasites such as isopods and copepods and internal parasitessuch as trematodes and nematodes were collected and studied.